2011
DOI: 10.1007/978-3-642-22300-6_35
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bounds for Maximally Greedy Binary Search Trees

Abstract: At SODA 2009, Demaine et al. presented a novel connection between binary search trees (BSTs) and subsets of points on the plane. This connection was independently discovered by Derryberry et al. As part of their results, Demaine et al. considered GreedyFuture,an offline BST algorithm that greedily rearranges the search path to minimize the cost of future searches. They showed that GreedyFuture is actually an online algorithm in their geometric view, and that there is a way to turn GreedyFuture into an online B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…, and hence splay is approximately monotone on all such executions. 21 Exactly the same logic applies to executions also containing Remark 2.5. The proof of the dynamic finger theorem given in [13,12] is notoriously complicated.…”
Section: Sequences Of Increments and Decrementsmentioning
confidence: 89%
“…, and hence splay is approximately monotone on all such executions. 21 Exactly the same logic applies to executions also containing Remark 2.5. The proof of the dynamic finger theorem given in [13,12] is notoriously complicated.…”
Section: Sequences Of Increments and Decrementsmentioning
confidence: 89%
“…The left-depth of every sub-root decreases from smallest to largest. 8 3. The splay operation takes constant amortized time.…”
Section: Postordersmentioning
confidence: 99%
“…Balanced TreesLet |x| denote the size of the subtree rooted at x. Following[18], we say T is α weight balanced for α ∈ (0, 1/2] if min{| left(x)|, | right(x)|} + 1 ≥ α · (|x| + 1)8 The first two invariants dictate that the ancestors of sub-roots form a right-toothed comb.…”
mentioning
confidence: 99%
“…However, the conversion in the other direction does not preserve online-ness. The method used by Fox [Fox11] to turn a particular online ASS superset algorithm into an online BST algorithm could probably be adapted to turn any online ASS superset algorithm into an online BST algorithm.…”
Section: Geometric Viewmentioning
confidence: 99%
“…While this method seems intuitively to be a good idea, basic facts like O(log n) amortized time per search were not known until the work of Fox [Fox11], who also showed that there is an equivalent online BST to this method. Showing that this method which greedily looks into the future has an equivalent online method provides some support for the belief that the best online and offline BST algorithms have asymptotically the same runtime.…”
Section: Greedymentioning
confidence: 99%